2021
DOI: 10.4014/jmb.2008.08027
|View full text |Cite
|
Sign up to set email alerts
|

Undecanoic Acid, Lauric Acid, and N-Tridecanoic Acid Inhibit Escherichia coli Persistence and Biofilm Formation

Abstract: Persister cell formation and biofilms of pathogens are extensively involved in the development of chronic infectious diseases. Eradicating persister cells is challenging, owing to their tolerance to conventional antibiotics, which cannot kill cells in a metabolically dormant state. A high frequency of persisters in biofilms makes inactivating biofilm cells more difficult, because the biofilm matrix inhibits antibiotic penetration. Fatty acids may be promising candidates as antipersister or antibiofilm agents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The SHDE extract also showed a relatively rich proportion of various fatty acids, of which the most significant content was found in the case of tridecanoic acid and pentadecanoic acid (see Table 3). Previous studies have confirmed the antimicrobial effects of these fatty acids against various microorganisms [38][39][40]. It can also be assumed that the overall antimicrobial effect of the areca nut extract is significantly affected by the fatty acid content.…”
Section: Antimicrobial Effect Of Distillation Fractions Of Areca Nutmentioning
confidence: 78%
“…The SHDE extract also showed a relatively rich proportion of various fatty acids, of which the most significant content was found in the case of tridecanoic acid and pentadecanoic acid (see Table 3). Previous studies have confirmed the antimicrobial effects of these fatty acids against various microorganisms [38][39][40]. It can also be assumed that the overall antimicrobial effect of the areca nut extract is significantly affected by the fatty acid content.…”
Section: Antimicrobial Effect Of Distillation Fractions Of Areca Nutmentioning
confidence: 78%
“…Glycerol monolaurate has a potent antimicrobial activity, and LA has the ability to convert into GML, which can destroy the lipid membrane of bacteria ( Jin et al, 2021 ). The high levels of activity of capric and lauric acids, and particularly that of monocaprin, are notable and suggest that these lipids have specific antichlamydial activities ( Bergsson et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…MCFAs are important substrates in mammalian energy metabolism and synthesis, and can also improve immune and in ammatory responses in intestinal cell lines [70,71]. For example, lauric acid inhibits a variety of pathogens, including E. coli, can signi cantly reduce in ammatory responses, and improves serum levels of in ammatory cytokines IL-6, TNF-α, IL-4, and IL-10 [72,73]. When the intestinal ora is in a healthy state, the body maintains an environment suitable for nutrient metabolite absorption.…”
Section: Discussionmentioning
confidence: 99%